EXTERNAL FACTORS WITH GOVERNMENT AND COMPANY POLICIES THAT HAVE AN IMPACT ON THE DEBT SERVICE COVERAGE RATIO OF COAL COMPANIES - Hermawan, Irwan; Sinaga, Bonar M.; Andati, Trias (Jurnal Aplikasi Manajemen, 2020)
Coal companies are industries that require large capital in building their industries, therefore companies must be able to know what external factors and internal factors that can affect financial performance and DSCR. This study uses a quantitative approach with secondary data from 4 coal companies listed on the IDX in 2011-2018. In this study structural and identity, equations are used with the 2SLS method. The results showed that (1) DSCR conditions, companies that had financial flexibility, with DSCR above the minimum requirements namely ADRO, INDY, and PTBA but BYAN did not have (2) the number of coal exports was influenced by the difference in Chinese GDP and the number of export coal sales, the number of domestic coal sales is influenced by differences in Indonesian GDP and the number of domestic coal sales. EBIT which is the company's profitability performance is affected by gross profit. FCF is the company's liquidity performance which is influenced by EBITDA and CAPEX. Principal payments are the company's liquidity performance that is affected by liabilities. DSCR, corporate solvency performance is influenced by the principal payment ratio, (3) the decline in Chinese GDP is anticipated by lowering production costs, general and administrative costs, sales and marketing costs, and CAPEX, have an impact on increasing the financial flexibility of the company and its DSCR. If The amount of DMO is added and the domestic coal price was set by the government or by market price, it impacted on increasing the financial flexibility of the company and its DSCR.